International portfolio optimisation under uncertainty - Chatsanga, Nonthachote (2017)
Portfolio optimisation problems are generally concerned with allocating funds to investments. The goal is to find an allocation that minimises risk subject to some certain constraints. To attain robust solutions from the optimisation, it is vital to ensure that the model is able to properly represent the underlying uncertainty in portfolio management.